2017
DOI: 10.3390/nu9010087
|View full text |Cite
|
Sign up to set email alerts
|

Effects of 1,25(OH)2D3 on Cancer Cells and Potential Applications in Combination with Established and Putative Anti-Cancer Agents

Abstract: The diverse effects of 1,25-dihydroxyvitamin D3 (1,25(OH)2D3), the bio-active form of vitamin D, on cancer cell metabolism and proliferation has made it an interesting candidate as a supporting therapeutic option in cancer treatment. An important strategy in cancer therapy is the use of combination chemotherapy to overcome drug resistance associated with numerous anti-cancer agents and to provide better means of avoiding undesirable side effects. This complex strategy is widely adopted by oncologists and sever… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 53 publications
0
11
0
Order By: Relevance
“…Previous studies have shown that active vitamin D metabolites can inhibit cell proliferation and/or cell survival in various tumour types from different tissues [29]. Studies on the effects of active vitamin D in different cancer cell lines indicate effects on proliferation in some cell types but not in others [30].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that active vitamin D metabolites can inhibit cell proliferation and/or cell survival in various tumour types from different tissues [29]. Studies on the effects of active vitamin D in different cancer cell lines indicate effects on proliferation in some cell types but not in others [30].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, 1,25D3 has been shown to induce genomic as well as rapid, non‐genomic effects that lead to regulation of cancer cell proliferation and survival . Furthermore, several studies have shown enhanced anti‐tumor effects upon combining 1,25D3 with established chemotherapeutics, such as anti‐metabolites, namely gemcitabine and 5‐fluorouracil, as well as platinum‐based drugs, for example, cisplatin and oxaliplatin . Another promising combination is the 1,25D3‐metformin combination, which has shown advantageous effects in different tumor models compared to either molecule alone …”
Section: Discussionmentioning
confidence: 99%
“…10 Furthermore, several studies have shown enhanced antitumor effects upon combining 1,25D3 with established chemotherapeutics, such as anti-metabolites, namely gemcitabine and 5fluorouracil, as well as platinum-based drugs, for example, cisplatin and oxaliplatin. 34 Another promising combination is the 1,25D3-metformin combination, which has shown advantageous effects in different tumor models compared to either molecule alone. 34 The impact of p53 on the chemo-and radio-sensitivity of cancer cells has been previously shown, with different reports showing a context-dependent impact of p53 status on cellular outcome.…”
Section: Expression Of Wnt/ β-Catenin Signaling Players Is Differenmentioning
confidence: 99%
See 1 more Smart Citation
“…With regards to cancer, large clinical trials are underway to assess the molecule’s therapeutic utility, whereas in vitro and in vivo studies have largely demonstrated profound anti-tumor potential associated with the active form [ 19 , 20 ]. Additionally, 1,25(OH) 2 D 3 and its analogues have been shown to be promising candidates for combination chemotherapy [ 21 ], due to their ability to augment the effects of conventional anti-cancer drugs including various anti-metabolites and platinum-based drugs.…”
Section: Anti-cancer Effects Of Vitamin D: Possible Regulation Of mentioning
confidence: 99%